Numerical analysis on the sloshing of free oil liquid surface based on fuel tanks of different shapes. (September 2020) - Zhang, Enhui; He, Ren
The shape of fuel tank is one of the main factors influencing oil liquid sloshing in fuel tank without baffles. The change of oil liquid sloshing pressure and free oil liquid surface area in fuel tanks of different shapes is the focus of this study. First, the reliability of the simulation method is verified by the test. Second, three different shapes of fuel tanks, which are rectangle, ellipse, and triangle, are proposed, and each shape of fuel tank is improved. A series of simulations are carried out under the same condition. The related history curves of oil liquid sloshing pressure and free oil liquid surface area are obtained, and the pressure contours of oil liquid sloshing and position diagrams of free oil liquid surface are displayed in the process of oil liquid sloshing. Finally, simulation data are compared and analyzed. In three different shapes of fuel tanks, it is found that the pressure of oil liquid sloshing in elliptical fuel tank is the biggest and time-area value of free oil liquid surface area in triangular fuel tank is the smallest. The curved bottom wall of fuel tank is beneficial to reduce the pressure amplitude of oil liquid sloshing and time-area value. All things considered, the heart-shaped fuel tank is optimal for reducing the pressure amplitude of oil liquid sloshing and evaporative emission under the same condition.